Mental Health, Substance Abuse, Co-occurring Disorders, and 3-Year Recidivism of Felony Parolees. (September 2019) - Houser, Kimberly A.; Saum, Christine A.; Hiller, Matthew L.
Having a mental health, substance use, or co-occurring disorder (COD) can make successful reintegration a difficult process for returning offenders. However, our understanding of how these disorders varies as far as their impact on recidivism during the reentry stage is lacking. Using a sample of 4, 381 parolees released to the City of Philadelphia, this study assessed how disorder type may influence repeat criminal offending by examining the independent effects of mental illness, substance abuse/dependence, and CODs on recidivism controlling for individual and neighborhood contextual factors and nonresidential land uses. In addition, we separated our measure of recidivism into two categories, re-incarceration for a new offense and re-incarceration for a parole violation to see whether different predictors emerged. Our findings showed that there were indeed differences according to disorder type, as well as between neighborhood variables and these findings also varied according to reason for incarceration. Moreover, we found evidence contrary to the assumption that COD offenders would have the worst outcomes due to the comorbid nature of their disorders.